THE SOCIAL NECESSITY AND MAIN FEATURES OF CORPUS LINGUISTICS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Many prominent scholars (Sinclair, Leech, Bieber, Francis, Johnson, Conrad, Hunston and McCarthy, etc.) have been involved in corpus linguistics and have played a major role in its development. Of course, we have considered the work of only a few of them. These scholars have made significant contributions to the field of corpus linguistics, both in the past and in the present, and their conclusions on the characteristics of corpuses, or important elements that distinguish a corpus from the Internet, have been considered in our article. Many corpus scholars consider John Sinclair to be one of the most influential scholars of modern corpus linguists. Sinclair established that a word does not have meaning by itself, but that this meaning is often carried out through the sequence of words that accompany it [Sinclair, 1991]. This idea served as the basis of corpus linguistics.